A Fallacy Analysis of the Arguments on the First U.S. Presidential Debate Between Hillary Clinton and Donald Trump - Jennifer Marella Santoso (Institute of Research and Community Outreach - Petra Christian University, 2017)
This research studies the fallacy in the arguments on the first 2016 U.S. presidential debate between Hillary Clinton and Donald Trump. This research is aimed to find out the fallacies occurred in the debate, the dominant fallacy made by each candidate, and the similarities and differences in each candidate’s fallacy. The topic on fallacy is chosen because fallacies are persuasive, yet misleading arguments which might contribute on influencing the people’s vote. In analyzing the data, the writer used the theory of arguments by Bierman and Assali (1996) and the theory of fallacy by Inch and Warnick (2011). From the total of 22 arguments, four of which are sound arguments. There is a total of 25 fallacies falling into six types which occurred. The most frequently occurred fallacy type is the “straw person” while the “audience-based” category becomes the dominant fallacy category. Furthermore, the writer found that Clinton made all of the sound arguments while Trump made all of the “hasty generalization” and the “ad populum” fallacy.